El “milagro de Bush”: la iniciativa del Millennium Challenge Account y su repercusión para la lucha contra la pobreza - Illán Sailer, Carlos (Revista Española de Desarrollo y Cooperación, 2023)
Amid growing criticism of aid effectiveness, the Bush administration is ready to implement what is called, according to its officials, a “new paradigm” of Development Assistance for the 21th Century. The initiative is called The Millennium Challenge Account, which aims to promote growth productivity with new resources channelled through the World Bank while reducing, at the same time, poverty in countries that comply with three “guiding principles”: good governance, investment in people and economic freedom. The article focuses on the negative effects that such initiative may bring about to the international co-operation system as well as to other experiences that have been launched to tackle the roots of poverty. While presenting itself as a positive innovation, the MCA could serve as part of the U.S.A security and foreign policy.